Assessment of drug-drug interactions in hypertensive patients at a superspeciality hospital - Divya Sivva; Uday Venkat Mateti; Venu Madhav Neerati; Nimbagiri Swamy Thiruthopu; Srinivas Martha (Avicenna Journal of Medicine, 2015)
Objective: The objective of the study was to assess the incidence and pattern of drug-drug interactions (DDIs) in hypertensive patients by using Micromedex and Medscape databases. Materials and Methods: A prospective observational study was carried out in a superspeciality hospital setting in South India for period of 9 months. Hypertensive patients who admitted into the hospital with the age more than 18 years, received more than 3 drugs per prescription and length of hospital stay for more than 24 hours were included in the study. An appropriate data was collected and assessed for DDIs with the help of Micromedex and Medscape databases. Results: A total of 227 patients were enrolled during the study period. Among the 227 patients, 48 of them developed 53 clinically significant DDIs. Out of 48 patients, most of them were in the age-group of 50-60 years [18 (37.49%)]. The percentage of DDIs were higher in males [30 (62.5%)] compared to females [18 (37.5%)]. The most common drugs responsible for DDIs in the present study were Insulin [18 (33.96%)] followed by Metoprolol [10 (18.86%)], Torsemide [8 (15.09%)], and Hydrochlorothiazide [8 (15.09%)]. The most commonly interacting pairs were Ciprofloxacin-Insulin [6 (11.32%)], followed by Metoprolol-Insulin [4 (7.54%)] and Atenolol-Insulin [4 (7.54%)]. The most common consequences of interacting pairs were reduced serum potassium levels and hyperglycemia. Conclusion: The overall incidence rate of DDIs was found to be 21.14% and the increasing number of co-morbidities ( P ≤ 0.003) and polypharmacy ( P ≤ 0.002) were the risk factor for the development of significant number of DDIs.